The changing role of women executives in the recording industry - Parsons, Patrick R. (Popular Music and Society, 1988)
Publisher: Routledge _eprint: https://doi.org/10.1080/03007768808591332

Women and Rock Music - Harding, Deborah; Nett, Emily (Atlantis: Critical Studies in Gender, Culture & Social Justice, 1984)
Rock music is the most misogynistic and aggressive form of music currently listened to. Women's place in it since the 1950's is described and analyzed in this article. Rock music was originally a working-class male challenge to the established symbolic order. In terms of the revenue generated by the industry thirty years later, it is the most important cultural expression of popular music. The enterprise is almost exclusively male, the majority of listeners are male, and even though women singers contributed in the early 1960's, there have been only a few female performers. An analysis of feminine representations in rock music lyrics and album covers in 1981 reveals a variety of male-identified images of women. In view of the cultural context in which rock music originated and the industry developed, the recent penetration by a few more women into the industry raises questions about whether numbers will continue to increase and, even if they do, whether rock music constitutes an appropriate voice in which women can authentically express themselves.
Number: 1
Keywords: Music; Myriam; Rock Music